Completion Rates of Advance Directives in a Trauma Emergency Room: Association with Age - Jan A. Graw; René Burchard (Emergency Medicine International)
Introduction An advance directive (AD) is a written legal document in which a person can express wishes and preferences for medical treatment for the moment when that person is no longer able to make medical decisions because of a serious illness or injury. While ADs have emerged in public, it is unclear, how many adults in Germany have completed an AD, and frequencies differ among different patient cohorts and medical settings. The aim of this study was to evaluate how many patients visiting a trauma emergency room (ER) in an academic teaching hospital had completed an AD. Furthermore, patient characteristics were compared between patients who had completed an AD and those who had not completed an AD. Methods. Patients with a traumatic injury or disease who attended the ER of an academic teaching hospital in the period from October 2015 to March 2016 (n = 499) were surveyed for completion rates of ADs. Results. Prior to their visit to the ER, 12.8% of the included patients possessed a completed AD. Patients with a completed AD had a higher age (median age: 54 (IQR: 34–66) vs. 35 (IQR: 25–50) p<0.001) and were less often living in an urban residential location (UR) (UR: 23.5% vs. 39.4%, p=0.029). Groups did not differ between sex (p=0.115), frequencies of high school graduates (p=0.482), and possession of a private health insurance (p=0.072), disability insurance (p=0.291), or an accident insurance (p=0.790). Conclusion. Completion rates of ADs remain low among patients visiting an ER of an academic teaching hospital in Germany. Increasing age but not factors such as sex, educational background, or insurance status were associated with a higher frequency of completed ADs.